2023
DOI: 10.1039/d3ta01621h
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry matters: correlation between antisite defects, microstructure and magnetic behavior in the cathode material Li1−zNi1+zO2

Abstract: As contemporary battery applications such as electric vehicles demand higher energy densities, layered LiNiO2 (LNO) could contribute as the end-member of the LiNi1-x-yCoxMnyO2 (NCM) family with the highest extractable specific...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…However, as discussed above, the formation of a perfectly layered structure is unlikely to occur via solid-state synthesis, i.e. a small amount of residual Ni is always observed to be present on the Li site (off-stoichiometry z, or Li deficiency) (Bianchini et al, 2019;Croguennec et al, 2009;Goonetilleke et al, 2023). In the diffraction data shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…However, as discussed above, the formation of a perfectly layered structure is unlikely to occur via solid-state synthesis, i.e. a small amount of residual Ni is always observed to be present on the Li site (off-stoichiometry z, or Li deficiency) (Bianchini et al, 2019;Croguennec et al, 2009;Goonetilleke et al, 2023). In the diffraction data shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…148 Alternatively, magnetic characterization can provide a complementary method to determine Li + /Ni 2+ cation mixing character, as the presence of excess Ni 2+ in the lithium layer is known to be correlated with magnetic ordering and the coupling of different nickel layers. 149,150 Xin et al showed magnetic susceptibility studies for Nb-modified NCM exposed to different temperatures. The Curie–Weiss behavior exhibited a magnetic transition at 10 K in pristine and doped NCM samples treated at 400 and 500 °C.…”
Section: Dopingmentioning
confidence: 99%
“…Second, LNO formation could be hindered due to the greater ionic radius of Ni 2+ (0.69 Å) relative to Co 3+ (0.545 Å) and Mn 4+ (0.53 Å), which could lead to more limited Brownian diffusion in the melt, thus crystal growth during synthesis. Regardless, other work 62 notes that materials with fractions greater than 10%, as seen in Fig. 4 for NaCl–Na 2 SO 4 (+), have suppressed particle growth, which deviates from more stoichiometric samples, as seen in Fig.…”
mentioning
confidence: 92%